2021
DOI: 10.1016/j.ssci.2021.105415
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of COVID-19 non-pharmaceutical interventions in long term care facilities in Cyprus: Safety improvement strategy

Abstract: The current COVID-19 crisis has changed our everyday lives almost in every aspect. Many people worldwide have died or hospitalised due to the severe impact of COVID-19 on the vulnerable population, and in particular to the elderly residents of long term care facilities (LTCF). The problem is amplified due to the fact that many of those occupants also suffer from comorbidities (e.g. respiratory and cardiovascular diseases, hypertension, etc.) and are therefore regarded as a susceptible host to severe COVID-19 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…RenderX and nursing homes. Previous studies have shown an association between a decrease in the number of COVID-19 cases and the rigor of various containment measures, notably school and workplace closures, and public information campaigns globally [19,20]. In HK, border restrictions, quarantine and isolation, social distancing, and behavioral changes in the population were significantly linked to the control of the COVID-19 pandemic [21].…”
Section: Xsl • Fomentioning
confidence: 92%
“…RenderX and nursing homes. Previous studies have shown an association between a decrease in the number of COVID-19 cases and the rigor of various containment measures, notably school and workplace closures, and public information campaigns globally [19,20]. In HK, border restrictions, quarantine and isolation, social distancing, and behavioral changes in the population were significantly linked to the control of the COVID-19 pandemic [21].…”
Section: Xsl • Fomentioning
confidence: 92%
“…Overall, it appears that there were lower rates of SARS-CoV-2 infection in facilities with greater infection prevention and control measures. 130,131 Similarly, in studies from the first wave, facilities with personal protective equipment shortages were more likely to experience SARS-CoV-2 outbreaks, 144 with proper training of staff in the use of personal protective equipment crucial in reducing SARS-CoV-2 transmission. 133 Importantly, modeling studies in nursing homes suggest an ongoing need for appropriate nonpharmacologic interventions even following the introduction of widespread vaccination, and lack of adherence to appropriate infection prevention and control procedures and provision or use of personal protective equipment in outbreak settings may mitigate some of the benefit of vaccination among residents.…”
Section: Nonpharmacologic and Infection Control Measuresmentioning
confidence: 99%
“…Local entities were involved as needed to promote the VACCELERATE Volunteer Registry. [25] The European Patients Forum (EPF) was invited to share the perspective of EU patient advocacy groups and to discuss per-country requirements, challenges, and commonalities of participating in the Volunteer Registry. [26] .…”
Section: Registry Progress and Outlookmentioning
confidence: 99%